Activation of the AKT-mTOR pathway confers selpercatinib resistance in thyroid cancer cells harboring the CCDC6-RET fusion gene - Amitani, Masatsugu; Shimizu, Tadafumi; Oba, Takaaki; Kawamura, Masaki; Ito, Ken-ichi (Biochemistry and biophysics reports, 2025)
Treatment strategies based on genetic alterations have been recently developed for the treatment of advanced or metastatic thyroid cancer. RET inhibitors are used to treat thyroid cancer with rearranged during transfection (RET) gene alterations; however, the emergence of drug resistance challenges effective treatment. Therefore, we aimed to elucidate the mechanisms underlying resistance to the RET inhibitor, selpercatinib. We used the papillary carcinoma cell lines, TPC-1 and CUTC48, which harbor the CCDC6-RET fusion gene. We established a selpercatinib-resistant subline (TPC-1/SELR) in TPC-1 via long-term exposure to selpercatinib. The growth-inhibitory effects of the drugs were analyzed using the WST assay. Changes in intracellular signal transduction were analyzed using western blotting. The 50 % inhibitory concentration (IC50) of selpercatinib in TPC-1 cells was 3 nM; however, growth inhibition in TPC-1/SELR and CUTC48 cells did not reach 50 % even at concentrations >100 nM. TPC-1/SELR cells showed increased phosphorylation of EGFR, ERK, AKT, and mTOR compared with that in TPC-1 cells. In CUTC48 cells, the phosphorylation of EGFR and ERK did not increase, whereas that of AKT and mTOR did. We investigated the growth-inhibitory effects of everolimus, an mTOR inhibitor, and found that TPC-1, TPC-1/SELR, and CUTC48 cells were highly sensitive to the drug. Our results suggest the involvement of AKT-mTOR pathway activation in selpercatinib resistance in thyroid cancer and that inhibition of the AKT-mTOR pathway may have therapeutic potential to overcome selpercatinib resistance. •Some selpercatinib-resistant thyroid cancers show enhanced AKT-mTOR pathway activation.•AKT-mTOR pathway may be involved in selpercatinib resistance of thyroid cancers.•Selpercatinib-resistant thyroid cancers are sensitive to mTOR inhibitor everolimus.•Inhibiting the AKT-mTOR pathway may overcome selpercatinib resistance.